2005
DOI: 10.1021/tx0502488
|View full text |Cite
|
Sign up to set email alerts
|

Competing Roles of Aldo-Keto Reductase 1A1 and Cytochrome P4501B1 in Benzo[a]pyrene-7,8-diol Activation in Human Bronchoalveolar H358 Cells:  Role of AKRs in P4501B1 Induction

Abstract: Benzo[a]pyrene (BP) requires metabolic activation to electrophiles to exert its deleterious effects. We compared the respective roles of aldo-keto reductase 1A1 (AKR1A1, aldehyde reductase) and P4501B1 in the formation of BP-7,8-dione and BP-tetrols, respectively, in intact bronchoalveolar cells manipulated to express either enzyme. Metabolite formation was confirmed by HPLC/MS and quantitatively measured by HPLC/UV/beta-RAM. In TCDD-treated H358 cells (P4501B1 expression), the anti-BPDE hydrolysis product BP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
2
39
1
Order By: Relevance
“…Our recent metabolism studies showed that the P450 1A1/1B1 and the AKR pathways can effectively compete for B[a]P-7,8-transdihydrodiol activation in AKR1A1 stably transfected H358 cells (19). In the present work, we exploited A549 cells because they have high constitutive expression of AKR1C1-1C3 isoforms (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent metabolism studies showed that the P450 1A1/1B1 and the AKR pathways can effectively compete for B[a]P-7,8-transdihydrodiol activation in AKR1A1 stably transfected H358 cells (19). In the present work, we exploited A549 cells because they have high constitutive expression of AKR1C1-1C3 isoforms (20).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al (18,19) In the A549 cell extracts B[a]P-7,8-trans-dihydrodiol was converted to B[a]P-7,8-dione, which was trapped with ␤-mercaptoethanol in situ as a thio-ether conjugate. The conjugate was identified by coelution with an authentic synthetic standard that was characterized by LC-atmospheric pressure chemical ionization (APCI)/MS, as described ( Fig.…”
Section: Anti-b[a]pde}mentioning
confidence: 99%
See 1 more Smart Citation
“…27, 28). The AKR-generated B[a]P-7,8-dione is a ligand for the aryl hydrocarbon receptor and will induce CYP1A1 and CYP1B1 still further (29,30). Moreover, the B[a]P-7,8-dione and the reactive oxygen species it generates induce AKR1C1-AKR1C3 genes via their antioxidant response elements (31,32).…”
Section: Significance For Cancer Etiologymentioning
confidence: 99%
“…The competing roles of P4501A1/1B1 and AKR1A1 in the metabolic activation of B[a]P-7,8-dihydrodiol has been examined in H358 cells manipulated to express either enzyme system. We found that AKR1A1 had a dual effect: it oxidized (-)-B[a]P-7,8-dihydrodiol to B[a]P-7,8-dione, but B[a]P-7,8-dione also acted as a ligand for the AhR leading to the induction of the P4501B1 gene (47). Thus, the P450 pathway generates metabolites that induce the AKR pathway and vice versa.…”
Section: Introductionmentioning
confidence: 97%